PENGARUH KONFLIK KERJA DAN LINGKUNGAN KERJA NON FISIK TERHADAP KINERJA KARYAWAN PATRA SEMARANG HOTEL DAN CONVENTION (Studi Kasus Pada Karyawan Patra Semarang Hotel Dan Convention ) - Ainan, Mochamad; Marhendi, Mengku; Hadi, Syamsul (Universitas Boyolali, 2023)
Conflict that occurs the success of an organization is strongly influenced by the performance of individual employees. Every organization or company will always try to improve employee performance, with the hope that the company's goals will be achieved. Work conflicts that cause a lack of interaction between each employee, lack of a sense of brotherhood, dependence on one other party in doing a job, differences in perceptions between each employee in completing tasks lead to work conflicts and not working hand in hand in completing work. The purpose of this study, namely: To determine the effect of work conflict and non-physical work environment on employee performance Patra Semarang Hotel & Convention . This type of research is quantitative descriptive research. The sample in this study was 150 respondents. researchers used multiple linear analysis.